Methods for solving inverse problems in mathematical physics - Prilepko, A. I. (Alekseĭ Ivanovich) (Monographs and textbooks in pure and applied mathematics, 2000)
Developing an approach to the question of existence, uniqueness and stability of solutions, this work presents a systematic elaboration of the theory of inverse problems for all principal types of partial differential equations. It covers up-to-date methods of linear and nonlinear analysis, the theory of differential equations in Banach spaces, applications of functional analysis, and semigroup theory.